Whose Bodies Matter? Exploring Historical Flows and Fractures in Indian Reproductive Norms - Sahgal, Ami; Sahgal, Smita (Advances in Social Sciences Research Journal, 2025)
Sexual and reproductive health (SRH), especially for women, continues to be stigmatised and silenced across cultures. The female body in Asia has long been a site of control, contestation, and power. As scholars suggest, it is embedded in a patriarchal arrangement of gender relations. Yet, this story is not a linear narrative. Religion, colonialism, caste, class, and capitalism, amongst other social forces, have continually reshaped gendered realities, producing distinct rights, struggles, and lived experiences across Asian nations. This paper examines India - the world’s most populous country - at the intersection of women’s SRH law(s), histories, and practice. India’s legal framework regarding SRH is comparatively liberal, but translating it from theory to practice requires our focus. To challenge patriarchal structures, it is necessary to trace their roots. Ancient Indian medical texts elucidate health issues, contain detailed medical treatises; however, the question stays. Were women’s needs ever conceptualised beyond fertility? By tracing continuities and ruptures in reproductive health discourse - from early expositions to contemporary debates and data figures on menstruation, reproduction, and abortion - we interrogate whether the female body has ever been truly centred on its own terms. The analysis bridges historical and sociological perspectives with field-based insights, mapping how rights-based narratives continue to challenge entrenched hierarchies. In doing so, we aim to offer a feminist vision for sustaining and democratising SRH rights and realities in India and beyond, in alignment with the SDG goals.